Factors Influencing Primary Care Follow-Up After Pediatric Mild Traumatic Brain Injury. Issue 4 (July 2019) - Currie, Dustin; Snedden, Traci; Pierpoint, Lauren; Comstock, R. Dawn; Grubenhoff, Joseph A.
Abstract : Objective: To identify socioeconomic, demographic, and caregiver factors associated with children attending primary care provider (PCP) follow-up after emergency department (ED) evaluation for mild traumatic brain injury (mTBI). Setting: Pediatric trauma center ED. Participants: Children 8 to 18 years of age sustaining mTBI less than 48 hours prior to an ED visit. Mean age of the 183 participants was 12 years with no significant differences between those who attended follow-up and those who did not in race, ethnicity, insurance provider, or PCP office setting. Design: Thirty-day longitudinal cohort study. Main Measures: Insurance type, PCP practice setting, and a caregiver attitudes survey regarding mTBI recovery and management (5 questions each scored on a 5-point Likert scale). The primary outcome was attending a PCP follow-up visit within 1 month of injury. Results: Females were more likely than males to attend PCP follow-up (adjusted odds ratio: 2.27 [95% confidence interval: 1.00-5.18]). Increasing scores on the caregiver attitudes survey indicating greater concerns about recovery were significantly associated with attending PCP follow-up (adjusted odds ratio: 1.12 per unit increase in composite score [95% confidence interval: 1.02-1.23]). No other socioeconomic, demographic, or injury characteristics were associated with attending PCP follow-up. Conclusions: The ED counseling regarding PCP follow-up of mTBI should stress the importance of follow-up care to monitor recovery and identify presence of lingering symptoms. Abstract : Supplemental Digital Content is Available in the Text.